Idealisme Mahasiswa Generasi Milenial dalam Karya Komik (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
The creator of a work of art with the title Idealism 'Millennial Generation Students in comics' was created as an effort to revive interest in the socio-political idealism of millennial students. Then create a socio-political themed comic with a combination of manga illustration style and Walt Disney cartoon digital painting. Comics are inspired by empirical experiences while active in the BEM FBS (2016-2017) and BEM UNJ (2017-2018) organizations. The socio-cultural conditions of the capitalistic commercial industry form students who display a relaxed, hedonistic, indifferent lifestyle, and position themselves more as part of a consumer society rather than being part of a civil society movement. Empirical experiences and socio-political books that have been read have become inspirations in making stories. Visual comics combines elements of manga and digital painting style coloring of Walt Disney cartoons. Comic works are printed and then presented in serial form, opened in 2 A5-sized volumes.